Answer: solve for x
x=
![(y-2)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/n2ihcef5zp6d6slogyo5m5k4wgv7pfbf4g.png)
solve for y
y=3x+2
Explanation:
solve for x
2y=6x+4
Swap sides so that all variable terms are on the left hand side.
6x+4=2y
Subtract 4 from both sides.
6x=2y−4
Divide both sides by 6.
6
6x
Dividing by 6 undoes the multiplication by 6.
![x=(2y-4)/(6)](https://img.qammunity.org/2023/formulas/mathematics/college/7h1y1j6nrj5nf9jgsmixct6w81i3gmt4r8.png)
Divide −4+2y by 6.
x=
![(y-2)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/n2ihcef5zp6d6slogyo5m5k4wgv7pfbf4g.png)
solve for y
2y=6x+4
The equation is in standard form.
2y=6x+4
Divide both sides by 2.
![(2y+2)/(2) =(6x+4)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/p4gkqsbxeiy94dzjlhu4zvfjdmqizdk2do.png)
Dividing by 2 undoes the multiplication by 2.
![y=(6x+4)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/l0gib3xxknvd2d35m61jehix2kz3jg82st.png)
Divide 6x+4 by 2.
y=3x+2